OS ISOTOPE SYSTEMATICS OF MESOARCHEAN CHROMITITE-PGE DEPOSITS IN THE SINGHBHUM CRATON (INDIA): IMPLICATIONS FOR THE EVOLUTION OF LITHOSPHERIC MANTLE - Mondal S.K.; Frei R.; Ripley E.M. (My University, 2007)
Os isotope studies of Mesoarchean (3.2 Ga) chromitite and associated gabbro-breccia hosted platinum-group element (PGE) deposits of the Singhbhum Craton in eastern India provide evidence for a complex history involving source mantle heterogeneity and hydrothermal processes. The average initial 187Os/ 188Os compositions of unaltered chromites of massive chromitite layers from two mining districts are 0.1031 +/- 0.0007 (Nuasahi) and 0.1029 +/- 0.0005 (Sukinda), with negative γOs values of - 1.78 +/- 0.65 and - 2.04 +/- 0.43, respectively. Mantle extraction ages (T MA) for these chromites indicate depletion from primitive mantle beginning as early as ~ 3.7 Ga, some 400 Ma before the crystallization of the respective chromites. The subchondritic signatures of Os in the studied chromites are comparable with results of age-constrained chromites from ultramafic intrusions in the Zimbabwe Craton [Nägler, T.F., Kramers, J.D., Kamber, B.S., Frei, R., Prendergast, M.D.A., 1997. Growth of subcontinental lithospheric mantle beneath Zimbabwe started at or before 3.8 Ga: Re-Os study on chromites. Geology 25, 983-986.], interpreted to reflect sequential extraction from evolving Archean subcontinental lithospheric mantle (SCLM). The similarity of depleted Os isotopic signatures of chromites from the Singhbhum Craton with those from the Zimbabwean occurrences, and their compatibility with the proposed Kaapvaal Craton SCLM model, leads us to propose that SCLM beneath the Singhbhum Craton also started to form in the early Archean. Up to now, early Archean continental crustal fragments, expected to have formed with the SCLM in the Singhbhum Craton have not been found, and early Archean detrital zircons [Mishra, S., Deomurari, M.P., Wiedenbeck, M., Goswami, J.N., Ray, S., Saha, A.K., 1999. 207Pb/ 206Pb zircon ages and the evolution of the Singhbhum Craton, eastern India: an ion microprobe study. Precambrian Res. 93, 139-151.] remain the only evidence for their existence. An alternative possibility is that the early Archean depleted mantle region could have remained within the convecting mantle for a few hundred million years before being added to the SCLM beneath the Singhbhum Craton. Re-Os isotopic data of chromites of massive chromitites from PGE and base metal sulfide (BMS) mineralized breccia zones are extremely heterogeneous. Perturbations of the Re-Os isotope systematics in these chromites are best explained as having resulted from interaction with hydrothermal fluids percolating in the shear zones, possibly genetically related to the emplacement of 3.1 Ga gabbroic suites. These fluids played a major role for the genesis and modification of the PGE mineralization. © 2007 Elsevier B.V. All rights reserved.
Keywords: ARCHEAN CHROMITE; CHROMITE; INDIA; RE-OS ISOTOPE; SCLM; SINGHBHUM CRATON; SM-ND ISOTOPE; Mesoarchean; Precambrian::Archean::Mesoarchean; Докембрий::Архей::Мезоархейская